Effect of Two Different Biochars as a Component of Compound Feed on Nutrient Digestibility and Performance Parameters in Growing Pigs - Schubert, Dana Carina; Chuppava, Bussarakam; Witte, Franziska; Terjung, Nino; Visscher, Christian (Frontiers in Animal Science, 2021)
The objective of this study was to examine two different biochars as a component of compound feed regarding their effects on nutrient digestibility and performance parameters in growing pigs. A total of 18 male, intact piglets (N = 18) with 26 days of age and an initial bodyweight of 6.88 kg were divided into three homogeneous groups of six animals each (n = 6). Treatments were control (CON, no addition of biochar), 2% biochar 1 (BC 1, diet containing 2% biochar 1), and 2% biochar 2 (BC 2, diet containing 2% biochar 2). Before the start of the trials, the biochars were characterized regarding Brunnauer-Emmet-Teller (BET) surface area, surface energy, humidity, and ash content. During the first trial (weeks 1–6) a 3 × 3 Latin square was used to determine the apparent total tract digestibility (ATTD) of all three feed in each animal (N = 54, n = 18). By start of the second trial on day 42, three new homogenous groups were formed with two animals from each of the previous groups. Each group received one of the three diets for 4 weeks. In the first trial, the ATTD of dry matter, organic matter, ether extract, crude fiber, and N-free extract was higher (p < 0.05) in pigs fed the biochar diets (BC1 and BC2) than in those animals fed the control diet. The greatest difference was found for ATTD of crude fiber, which was increased by 19.8 and 23.8%, respectively (CON: 30.8b ± 13.4%; BC 1: 38.4a ± 8.2%; BC 2: 40.4a ± 12.2%). ATTD of crude protein was only higher in BC 2 compared to CON (CON: 81.0b ± 4.1%; BC 1: 82.4ab ± 3.6%; BC 2: 84.2a ± 3.4%). In both trials, the different treatments revealed no effects on ADFI, ADWG or G:F (p > 0.05). The results indicate that no negative effects can be expected when 2% biochar is included in the feed for growing pigs.